Impact of Chlorpyrifos on Cytopathological Indices in Mangrove Crab, Episesarma tetragonum (Fabricius) - Ravi, Rajesh; Athisuyambulingam, Maharajan; Kanagaraj, Shanmugavel; Tresnakova, Nikola; Impellitteri, Federica; Viswambaran, Ganapiriya; Faggio, Caterina (Veterinary sciences, 2023)
Chlorpyrifos is an organophosphate insecticide occurring in aquatic ecosystems. Due to exposure to xenobiotics, several harmful effects on aquatic organisms are noticed worldwide. Mangrove crabs are an ecologically important aquatic invertebrate species in food web interactions and in the mangrove ecosystem. Therefore, this study aimed to evaluate the cytotoxic effects of chlorpyrifos on the mangrove crab, Episesarma tetragonum. Crabs were exposed to 0.0294 and 0.0588 ppm of chlorpyrifos for 7 and 28 days. Cytopathologic effects on the gill, hepatopancreas, and muscle were investigated, and observations were compared with a control group. The results suggest that chlorpyrifos induces time- and concentration-dependent cytopathological alternations in the gill and exhibited epithelial lifting, oedema, necrosis, and a fusion of secondary lamellae and haemorrhage. The deceased hepatopancreas showed infiltration, a large lumen formation, and the disappearance of haemocytes, while the muscle tissue showed atrophy, necrosis, a wavy appearance, an accumulation of granular material between muscle fibres, and fragmentation in a mangrove crab. This study shows the great potential of cytopathological investigations, allows us to assess the sensitivity of various aquatic animal species to potentially dangerous compounds, and calculates safe concentrations with which to reduce pesticide use.
Keywords: crab; insecticide; cytotoxicity; chlorpyrifos; cytopathology